Melanosis Coli: Diagnosis, Clinical Significance, and Prognosis in Colorectal Screening - Sahil Sabharwal; Kemmian Johnson; Brandyn Young; Sarah Assem; Ragesh Thandassery (Iranian Journal of Colorectal Research)
Melanosis coli is a generally benign condition characterized by brown-black pigmentation of the colonicmucosa. It is classically associated with the prolonged use of anthraquinone laxatives, with senna and cascarabeing the most commonly utilized agents. The accumulation of the pigment lipofuscin within macrophages inthe colonic lamina propria has been observed with long-term use of anthranoid laxatives. This phenomenon isconsistent with the classic discoloration of the colon for which this condition is known, often observed duringcolonoscopy. The following case report focuses on a 55-year-old woman with a medical history that includeshypertension, uterine hypertrophy, menorrhagia, migraine, and constipation, who presented for a screeningcolonoscopy. It addresses the challenges in diagnosing melanosis coli and discusses its clinical significancebased on a review of the relevant literature. This case review and literature search summarize informationregarding the management and prognosis of melanosis coli in the context of colorectal cancer screening andthe detection of adenomas.